Quarantine time in Venice: 'Weaving thoughts' looking forward to a place to live together - Luca Caldironi (Archives of Depression and Anxiety - Peertechz Publications, 2020)
The title of the last Venice Biennale Art was May You Live in Interesting Times, and the title of the next Architectural Biennale is How Will We Live Together?